Trace Metals in Exchangeable Soil from the Oil Fields in Basrah Governorate, Iraq: Melacak Logam dalam Tanah yang Dapat Ditukar dari Ladang Minyak di Kegubernuran Basrah, Irak - Ahmed, Fatima J .; Alkafaji, Ayad H.; Al-Saad, Hamid T. (Universitas Muhammadiyah Sidoarjo, 2024)
Soil samples were collected from eleven locations (Seba, Safwan, Majnoon, Ratawi, Bergezia, West Qurna 2, West Qurna 1, Shuaaba, South Rumaila, North Rumaila, and Al Zubair) were selected in the oil fields at Basrah city .And measured of trace metals by Inconductivity Coupled Plasma (ICP). The analysis of trace element concentrations based on CF, EF , and Igeo reveals the following that Lead (Pb): Significant contamination is observed in West Qurna 2, with extremely high values across all indices. This indicates severe anthropogenic influence and requires immediate investigation and monitoring, Cadmium (Cd): Slight contamination is noted in West Qurna 1 and West Qurna 2, though the levels are generally within acceptable limits in other stations, And other Elements (Fe, Cu, Zn, Mn, Cr): These elements show natural concentrations across all stations, with no signs of significant enrichment or contamination. Highlights: Sampling: Soil collected from 11 Basrah oil field locations. Findings: High Pb in West Qurna 2; Cd slight contamination. Other Metals: Fe, Cu, Zn, Mn, Cr at natural concentrations.. Keywords: Basra , Basra oil fields, Exchangeable , Trace metals , Soil , ICP.